Evaluation for Elevation Angle-Dependent Beam Size in NR NTN Systems - Han, Sangmin; Shin, Wonjae; Kim, Jae Hyun (International Conference on ICT Convergence, 2023)
Appropriate beam design plays a vital role in satellite-based Non-Terrestrial Networks (NTN) towards beyond 5G. In this paper, we propose an evaluation for elevation angle-based major-semi axis beam radius. To deal with this, we calculate beam major semi-axis radius with elevation angle and differential delay in NTN, based on 3rd Generation Partnership Project (3GPP) New Radio (NR) standards. Using the evaluation method, within NR standards, the differential delay-based beam major semi-axis radius can be independent of the elevation angle in some elevation angle intervals. Furthermore, we compare the differential delay-based beam results with the 3dB beamwidth results. The comparison shows that the differential delay-based beam major semi-axis radius can be more critical according to the preamble structure, subcarrier spacing, and elevation angle.
Keywords: Beam size; Differential delays; Elevation angle; Elevation angle-based beam; Low earth orbit satellite network; Low earth orbit satellites; OFDM numerology; Preamble; Satellite network; Terrestrial networks; beam size; differential delay; elevation angle-based beam; Low Earth Orbit (LEO) satellite networks; OFDM numerology; preamble